RISK MANAGEMENT ANALYSIS IN CPO PRODUCTION (CASE STUDY OF PTPN IV REGIONAL I PKS SEI SILAU) - Nugraha, Hasybi Abdillah; Harahap, M Ikhsan; Atika (International Journal of Cultural and Social Science, 2025)
This study analyzes risk management in Crude Palm Oil (CPO) production with a case study at PTPN IV Regional I PKS Sei Silau. Palm oil is a major commodity in Sumatra with a significant contribution to the Indonesian economy, where this industry contributes 3.5% of the total national GDP and 13.5% of non-oil and gas exports. The purpose of the study was to identify risks in CPO production and determine risk management strategies. The research method used a descriptive qualitative approach with data collection through interviews and direct observation. Risk analysis was carried out using the Failure Mode and Effect Analysis (FMEA) method to identify, analyze, and evaluate risks. The results of the study showed five main sources of risk in CPO production, namely: shortage of FFB raw materials (18), sorting FFB with raw fruit (12), machine damage (60), delays in the production process (6), and substandard CPO quality (24). The mitigation strategies implemented include optimizing production machines, regular training for employees, and strict supervision during the production and distribution process. The implementation of these strategies has reduced raw material shortages by 30% and increased production efficiency. This study concludes that the systematic application of risk management can improve operational smoothness and the quality of CPO products.